Efficacy of oral L-arginine on amniotic fluid index in pregnant women with oligohydramnios attending antenatal clinic in a tertiary care hospital in Telangana, India - Begum, Md Amirunnisa; Krishna Sowmya, B.; Shailendra, D.; Subbaratnam, Y. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Oligohydramnios leads to feto-maternal morbidity and mortality. Though there is no specific treatment for oligohydramnios, use of L-arginine seems to be promising. As a nitric oxide donor, it causes vasodilatation, increases placental perfusion and finally increases amniotic fluid. However, data on the use of L-arginine for oligohydramnios is scarce. Hence, this study was aimed to evaluate the efficacy of oral L-arginine on Amniotic Fluid Index (AFI) and to document the pregnancy outcomes in women with oligohydramnios. Methods: This was a prospective observational study conducted on pregnant women attending antenatal clinic (ANC) at Mediciti Institute of Medical Sciences (MIMS), Ghanpur, Telangana, India from 1st January 2018 to 30th June 2018. Results: A total of 50 participants were enrolled and 4 participants among them were lost to follow- up. Mean age (SD) of the women enrolled was 23.3 (3.49) years. Mean gestational age (SD) at the time of diagnosis was 34.61 (1.53) weeks. Mean AFI (SD) at the time of diagnosis and after treatment with L-arginine were 6.8 (1.3) cm and 9.4 (2.82) cm respectively. After a mean treatment duration (SD) of 3.23 (1.38) weeks, a mean (SD) increase of AFI by 2.6 (1.57) cm (P <0.0001) was observed. An increase of AFI was noted in 84.78% of cases (P <0.0001). Mean (SD) Gestational age at the time of delivery was 38.25 (1.48) weeks. Only 37% of participants required operational deliveries. Mean (SD) birth weight of the new borns was 2.54 (0.47) kg. Neonatal Intensive Care Unit (NICU) admissions were required in 32.6% of new borns. Conclusions: L-arginine is efficacious in improving AFI in oligohydramnios. AFI improvement could possibly lead to better neonatal outcomes by reducing preterm deliveries and operative interventions.